Asymmetric and nonlinear oil price pass-through to economic growth in Croatia: Do oil-related policy shocks matter?. (June 2022) - Borozan, Djula; Lolic Cipcic, Marina
Abstract: Recent turbulent developments in the world oil market have increased the volatility of oil prices and rekindled interest in studying their impact on macroeconomic activity. Using the vector autoregression framework, this paper investigates the impact of oil price shocks, expressed in linear, asymmetric and nonlinear form, on real gross domestic product (GDP) growth in an oil-importing small open economy, i.e., Croatia, for the period 1995:Q1-2019:Q4. The results corroborate the presence of the asymmetric, nonlinear and direct short-run effect of oil price shocks on real GDP growth. A decrease in oil prices leads to a statistically significant increase in real GDP and its more volatile behavior, while an increase in oil prices causes a considerable drop in economic activity only in the fourth quarter. The oil-related policy shock variables, fuel market liberalization and fuel taxation, turned out to be insignificant predictors of GDP growth in an asymmetric and nonlinear model specification. Highlights: The pass-through of oil price shocks to economic activity is tested in a small and open economy. Oil price indicators are expressed in linear, asymmetric, and asymmetric and nonlinear form. The asymmetric, nonlinear and direct short-run effect of oil price shocks on economic activity is confirmed. Oil-related policy shock dummy variables are not important determinants of real GDP growth.